Modulating the physical properties of solid forms of urea using co-crystallization technology. Issue 37 (22nd March 2018) - Sandhu, Bhupinder; Sinha, Abhijeet S.; Desper, John; Aakeröy, Christer B.
Abstract : The solid-form landscape of urea was explored using full interaction maps (FIMs) and data from the CSD to develop optimum protocols for synthesizing co-crystals of urea. Abstract : The solid-form landscape of urea was explored using full interaction maps (FIMs) and data from the CSD to develop optimum protocols for synthesizing co-crystals of urea. As a result, 49 of the 60 attempted reactions produced new co-crystals, and the crystal structures of four of these are presented. Moreover, the goal of reducing the solubility and lowering the hygroscopicity of the parent compound was achieved, which in turn offers new opportunities for application as a slow-release fertilizer with limited hygroscopicity, thereby reducing many current problems of transport, handling, and storage of urea.